The Arab Gulf States and Japan : prospects for co-operation : proceedings of a Joint Symposium on the Energy Industries--Prospects of Co-operation Between Arab Gulf States and Japan (Croom Helm, 1986)
This book consists of the following many parts: security of oil supply, oil price, marketing, and other related issues, research and development, training, the economics of petrochemical industries, alternative energy sources, co-operation between arab gulf states and Japan.